TRANSFORMASI DIGITAL PERKERETAAPIAN DI EROPA DAN INDONESIA - Dahlan, Dahlan; Wibowo, Heriyanto; Arsyad, Muhammad Fahmi; Abdurachman, Aulia Azhar; Rachma Puspita, Sesaria Mardhiani (Institut Transportasi dan Logistik Trisakti, 2021)
The world of railways is entering the era of digitalization, this condition does’nt only occur in developed countries such as Europe, United States or China, but also in Indonesia. The development of technology cannot be separated from desire of the people who want practical services, for example in Indonesia people doesn’t want to be burdened with ticket purchases or manual administrative and management services which are very time consuming. Therefore, PT. MRT Jakarta and PT. KAI continues to improve technology-based products and services by providing best experience for customers. With the Industrial Revolution 4.0, it’s hoped it can help productivity and efficiency of railway industry in serving its customers and inspire various other industries to implement it. The purpose of this research is to see the development of railroad digitization that has occurred in Europe with developments that have been made in Indonesia. The method used in this research is qualitative and descriptive interview methods, interviews with several resource persons from the transportation sector by employees of PT. KAI and PT. MRT Jakarta. In addition, it’s also obtained from literature studies in the form of journals and sources from the internet to collect data related to the development of digital transformation that has been applied to the European railway system.